A story of disturbance and loss: historical coral reef degradation in Bahía Culebra, North Pacific of Costa Rica - Fabregat Malé, Sònia (2025)
Introduction: Climate change and other multiple stressors have globally caused the collapse of many coral reefs. Understanding how coral reefs have responded to previous disturbances is key to identify possible trajectories in the face of future more frequent and intense disturbances. Objective: We review the ecological history of coral reefs in Bahía Culebra, a historically important area for coral reef development in the North Pacific of Costa Rica, which has suffered extreme deterioration in the last decades. Methods: We assessed historical traits of coral reefs using both historical and recent data, divided as follows: (i) the “pre-disturbed” period (1970–2000), (ii) the early degradation period (2000–2010), and the degraded period (2010–present day). Results: Forty years ago, Bahía Culebra harbored the highest coral species richness in the Costa Rican Pacific, with high live coral cover (> 40 %). Signs of early degradation were observed after El Niño events and unprecedented coastal development that caused anthropic eutrophication, which led to coral death and a shift to macroalgae-dominated reefs. In the last decade, a steep decline in live coral cover (1–4 %), the loss of many reefs, and a decrease in reef fish diversity and abundance were recorded. Conclusions: To promote the recovery of coral reefs in the bay, we propose management actions such as marine spatial planning, mitigation and monitoring of stressors, and ecological restoration. The latter could help turn the tide by increasing live coral cover, eventually leading to ecosystem functionality recovery, with spill-over effects on reef-associated communities, including local coastal communities. Nonetheless, such actions need governmental and local support; thus, raising awareness through environmental education and citizen science programs is key for the long-needed conservation of coral reefs in Bahía Culebra.